Changing epidemiology of monkeypox and risk for wide-scale outbreak - Sora Yasri; Viroj Wiwanitkit (Wolters Kluwer Medknow Publications, 2022)
Monkeypox has spread over Europe, posing a major threat to public health. Monkeypox is a rare pox infection that has returned, with zoonosis suspected as the cause. Human-to-human transmission is now under observation. The medical community has been alerted by an increasing number of reported cases in several countries. SARS-CoV-2 pandemic taught us that in the event of an outbreak, we must act promptly to respond, examine thoroughly, and take appropriate action. Although monkeypox is an old disease, a new genetic mutation may have resulted in a more severe illness and a widespread outbreak.